2013
DOI: 10.1007/s11250-013-0393-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and non-genetics parameters of body weight for post-weaning traits in Raini Cashmere goats

Abstract: Genetic parameters were estimated for 6-month weight (W6), 9-month weight (W9), 12-month weight (W12), average daily gain from birth to 6 months old (ADG6), and Kleiber ratio at 6 months (KL6) traits using 6,442 records obtained from a Raini Cashmere goat flock. The parameters were estimated using the restricted maximum likelihood procedure and applying four animal models excluding or including maternal additive genetic and permanent environmental effects. Heritability estimates for W6, W9, W12, ADG6, and KL6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Higher estimates for genetic correlation for BWT with other traits than current study were reported by Gowane et al (2011) in Sirohi goat (0.20-0.47), Baneh et al (2012) in Naeini (0.49-0.61) and Barazandeh et al (2012) in Raini Cashmere goat (0.53-0.55). Genetic correlation estimates for WT3 and WT6 with other traits were in accordance with the findings of Gowane et al (2011) in Sirohi, Moghbeli et al (2013) in Raini Cashmere and Tesema et al (2020) in Boer x Central Highland goat.…”
Section: Discussionsupporting
confidence: 85%
“…Higher estimates for genetic correlation for BWT with other traits than current study were reported by Gowane et al (2011) in Sirohi goat (0.20-0.47), Baneh et al (2012) in Naeini (0.49-0.61) and Barazandeh et al (2012) in Raini Cashmere goat (0.53-0.55). Genetic correlation estimates for WT3 and WT6 with other traits were in accordance with the findings of Gowane et al (2011) in Sirohi, Moghbeli et al (2013) in Raini Cashmere and Tesema et al (2020) in Boer x Central Highland goat.…”
Section: Discussionsupporting
confidence: 85%
“…After domestication of their wild ancestors (bezoars), goats followed the spread of agriculture, reaching the Mediterranean 8 000 BP and north Africa 7 000 BP ( Daly et al, 2018 ; Zeder & Hesse, 2000 ). Currently, the global goat population has grown to more than one billion, and goat farming is a common animal production sector in many countries, especially in the Middle East and Mediterranean ( Gooki et al, 2018 , 2019 ; Moghbeli et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diversity is an essential element for genetic improvement, preserving populations, evaluation and adapting to variable environmental situations [ 15 , 16 ]. On other hands, determination of gene polymorphism is important in farm animal breeding [ 1 , 17 ] in order to define genotypes of animal and their associations with productive, reproductive and economic traits [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%